Cereal price transmission in Asia during the global food crisis - Dawe, David (2010)
International cereal prices in US dollar terms have been increasing since 2003, but it is domestic prices that affect food consumption and production, and thus, food security and supply response. Price transmission from international markets to domestic markets will be less than perfect given that the real exchange rate of many Asian countries has appreciated against the US dollar. In addition, country specific stabilization policies limit price transmission from international to domestic markets. This paper analyzes the extent to which international cereal price changes have been transmitted to domestic prices since 2003 in selected Asian countries. Given the interest in rising food prices around the word, this paper aims to stimulate substantial discussion on the subject matter. The methodology relies on calculation of real world prices, real exchange rates, and real domestic prices. The analysis is conducted for several cereals (rice, wheat, maize, etc.), as well as fertilizer prices. Further, price changes at different levels of the marketing system are analyzed to assess whether consumer price increases are being passed back to farmers, a necessary condition for there to be a supply response. It appears from the main points made in the paper that the incentives for Asian rice farmers have improved during the past few years. Nevertheless, the magnitude of the improved incentives is much less than the price increases reported on world markets due to: 1) less than perfect transmission of world prices to domestic markets; and 2) increases in input prices. Furthermore. the magnitude of supply elasticity and the magnitude of price increases for other farm commodities. Thus, the ultimate supply response is still subject to a great deal of uncertainty. Tentatively, it seems that Asian rice production will reach a new record in 2008, higher than even the record 2007 crop.
Keywords: Prices; Foreign exchange rates; Food prices